The Significance of Iqbal’s Educational Philosophy in the Construction of South Asian Muslim Nation State - Jugang, Li (Annals of Human and Social Sciences, 2023)
Iqbal is a famous poet, philosopher and politician in modern South Asia. His thoughts have a great influence on the whole Islamic world. Based on Islamic philosophy, Iqbal’s educational philosophy is centered on the construction of "Khudi" and the education of perfection based on monism. Iqbal elaborated on the four important elements of "ego": love (Ishq), detachment (Faqr), desire (Desire) and creative activity (Creative Activity), and advocated cultivating a perfect person with "ego" to promote the progress of the whole society. In Iqbal’s discussion on educational philosophy, he pointed out the problem of educational alienation in the whole South Asia at that time from a critical perspective, reflected on the problems arising from the local development of the western educational system, and conceived the future of Islamic education according to his educational philosophy. His views represent the process of modern Muslim intellectuals’ tortuous exploration of the modernization of their national education, and express their spiritual aspirations under the strong western civilization. Even today, his educational thoughts still have a profound impact on Islamic education in South Asia and even the world at the theoretical and practical levels.